(untitled) (Bangladesh Journal of Medical Science, 2022)
The biology of Cryptosporidium has been studied increasingly since it was recognized as a pathogen of humans more than a century. Its recent recognition as a second leading cause of diarrhoea or cryptosporidiosis immunocompromised patients globally has led many researchers to study on this parasite. Many new technologies such as high-throughput omics and bioinformatics tools have been implemented to investigate this zoonotic parasite in a better approach. The aim of this review article is mainly to briefly describe recent applications of structural bioinformatics in order to reveal the potentiality of a suitable therapeutic target in Cryptosporidium. This review was written based on the search of cited publications in SCOPUS website with the combination of word ‘Cryptosporidium’ with other words like bioinformatics, protein structure, structural biology and homology modeling. The search results then were selected based on the relativeness of updated information needed to be prepared in this review. Several cited publications were used to elaborate the review accordingly despitelimitedreviewupdatesrelatedtoprotein bioinformation of thisparasite. As a conclusion, bioinformatics is a commonly known to be cutting-edge technology that has been recognised for its power to reveal the secret of parasite biology in silico including a neglected parasite, Cryptosporidium. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 8-18